Meningkatkan Kesadaran Lingkungan Melalui Pelatihan Pembuatan Kursi Ecobrick - Retnoningsih; Mahmudah, Husnatul; Zuhrah; Zuhriyah, Nurul; Nurfitriani; Hidayatullah, Syarif (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2024)
Plastic waste is one of the significant environmental problems, especially in areas with minimal waste management. As an effort to increase environmental awareness while reducing the negative impact of plastic waste, training on making ecobrick-based chairs was carried out for women who are members of the Bima Regency Women's Organization Association (GOW). This activity was held on August 13, 2024 in the Hall of the Bima Regency PKK Building with a participatory approach. The training began with counseling on the impact of plastic waste and the introduction of the concept of ecobricks as an innovative and applicable solution. Furthermore, participants were involved in hands-on practice of making ecobrick chairs, from filling plastic bottles to assembling them into ready-to-use chairs. This activity was attended by participants from various women's organizations in Bima Regency. The results of the training showed that participants were able to understand and practice ecobrick chair making techniques well. In addition, this activity succeeded in increasing participants' awareness of the importance of plastic waste management. All participants stated that this training was informative, useful, and easy to apply in their homes. This training is expected to be the first step to create positive changes in plastic waste management in the community, as well as motivate participants to spread the concept of ecobricks as a sustainable solution in overcoming the problem of plastic waste